Extending floating catchment area methods to estimate future hospital bed capacity requirements. (November 2022) - Fowler, Daniel; Middleton, Paul; Lim, Samsung
Abstract: A new hospital in north-west Sydney, Australia is to start construction in the year 2023. However, the number of emergency department beds/treatment spaces (EDBs) that it will contain is yet to be determined, as this region is expected to have relatively high population growth from year 2021 to year 2036. In this paper, floating catchment area (FCA) methods were employed to estimate the required number of EDBs for this new hospital. Metrics including spatial accessibility index and spatial equity were calculated based on the predicted populations for 2021 and 2036 using government sourced data. Specifically, potential spatial accessibility and horizontal spatial equity were employed for this paper. Mathematical optimisation was used to determine the most efficient distribution of EDBs throughout different hospitals in this region in 2036. The best allocation of capacity across the study area that simultaneously improved average spatial accessibility and improved spatial equity relative to the metrics of 2021 was found. Traditional methods of healthcare planning seldom consider the spatial location of populations or the travel cost to hospitals. This paper presents a novel method to how capacity of future services are determined due to population growth. These results can be compared to traditional methods to access the validity of the methods outlined in this paper.